2011
DOI: 10.1590/s1984-82502011000100026
|View full text |Cite
|
Sign up to set email alerts
|

Drug analysis

Abstract: a n d m e t h o d s i n c h a r a c t e r i z a t i o n a n d d e e p s t u d i e s o n t h e polymorphic state of drug substances. The book is divided into six main sections: the first deals with thermodynamics and theoretical issues including characterization of polymorphic and solvatomorphic systems along with computational methodologies for prediction of the crystal polymorph state of drugs. The second section covers preparative methods for polymorphs and solvatomorphs, where the classical as well as High-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Askin et al designed a protocol to synthesize new imidazole [2,1b] [1,3,4]thiadiazoles (73)(74)(75)(76)(77)(78)(79)(80)(81). Initially substituted benzyl chloride derivatives (62)(63)(64) were refluxed with KOH in presence of ethanol for 4-6 h to obtain 2-amino-1,3,4-thiadiazoles (66)(67)(68) Newly synthesized compounds were tested for their inhibitory activity against hCA I and hCA II by taking standard AAZ and THA and it was observed that compound 70b and 71 were found to be most potent against hCA I with K i values of 23.44 ± 4.92 and 51.53 ± 10.74 nM, respectively.…”
Section: S C H E M E 7 Synthesis Of 42(a-l)mentioning
confidence: 99%
See 3 more Smart Citations
“…Askin et al designed a protocol to synthesize new imidazole [2,1b] [1,3,4]thiadiazoles (73)(74)(75)(76)(77)(78)(79)(80)(81). Initially substituted benzyl chloride derivatives (62)(63)(64) were refluxed with KOH in presence of ethanol for 4-6 h to obtain 2-amino-1,3,4-thiadiazoles (66)(67)(68) Newly synthesized compounds were tested for their inhibitory activity against hCA I and hCA II by taking standard AAZ and THA and it was observed that compound 70b and 71 were found to be most potent against hCA I with K i values of 23.44 ± 4.92 and 51.53 ± 10.74 nM, respectively.…”
Section: S C H E M E 7 Synthesis Of 42(a-l)mentioning
confidence: 99%
“…Initially, isatin derivatives 101(a-c) treated with KI and K 2 CO 3 in presence of DMF and were refluxed for 4-6 h to yield N-alkylated isatin derivatives 102(a-o) and were further reacted with thiosemicarbazide, 1,4-dioxane Cs 2 CO 3 along with refluxing to synthesize compounds N-alkylated triazino [5,6-b]indolethioether derivatives 103(a-o). Second, compounds 103(a-o) were reacted with propargyl bromide to produce compounds N-alkyl-3-prop-2-yn-1-ylthio)-5H- [1,2,4]triazino [5,6b] indole derivatives 104(a-o) followed by the reaction with Newly synthesized compounds 105(a-o) were screened for inhibitory activity against human (h) isoforms of CA, hCA I, II, XIII (cytosolic isoforms), and hCA IX (tumor related isoform) by the stopped-flow CO 2 hydrase assay method by taking AAZ as standard drug and it was observed that 105i (X = F, R = -CH (CH 3 ) 2 ) was found to show potent activity against hCA II and hCA XIII with K i values of 7.7 and 34.9 nM, respectively, as compared to AAZ (K i = 12.1 nM) due to the presence of fluoro-group at fifth position of indole moiety and isopropyl group attached to nitrogen of indole ring [34] (Scheme 15). (110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129).…”
Section: S C H E M E Synthesis Of 94(a-s)mentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing the literature extensively, different methods have been published for the determination of OLM and HCZ in their mixture. The binary mixture was analyzed by differrent spectrophotometric [6][7][8][9][10][11][12], spectrofluorimetric [13], electrophoretic [14], HPTLC [15][16][17][18], HPLC [15,[19][20][21][22][23][24][25][26][27][28][29][30][31], and UPLC [32,33] methods. The studied mixture was also determined in plasma by LC-MS [34][35][36].…”
Section: Introductionmentioning
confidence: 99%